Contrast enhanced computed tomography assessment of superficial inguinal lymph node metastasis in canine mammary gland tumors. Issue 5 (15th June 2021) - Soultani, Christina; Patsikas, Michail N.; Mayer, Monique; Kazakos, Georgios M.; Theodoridis, Theodoros D.; Vignoli, Massimo; Ilia, Tatiani Soultana M.; Karagiannopoulou, Maria; Ilia, Georgia M.; Tragoulia, Ioanna; Angelou, Vasileia N.; Chatzimisios, Kyriakos; et al.
Abstract: Mammary gland neoplasms are predominant in dogs. However, sentinel lymph node (SLN) status assessment criteria have not been established for these cases. In this retrospective, secondary analysis, diagnostic case control study, CT images of 65 superficial inguinal SLNs were obtained before and 1, 3, 5, and 10 min after intravenous administration of contrast agent (iopamidol 370 mgI/mL). The presence and degree of postcontrast enhancement were assessed, by means of the median absolute density value and the maximum absolute density value at any time point in the center and in the periphery of each SLN measured in Hounsfield units (HU), before and after contrast agent administration. These values were compared with histopathological findings postsurgical excision. Receiver operating characteristic analysis was conducted. The absolute density values ranged widely at each time point and within each group of nodes (negative, positive, control group). At all time points, the median density value in the center and in the periphery was significantly higher in metastatic than in non‐metastatic SLNs ( P ≤ .014). Among the parameters tested, the median absolute density value measured in the periphery of the SLN 3 min after injection showed the highest sensitivity, specificity, and accuracy (AUC) (87.5%, 82.1%, and 92.1% respectively), with a cutoff value of 50.9 HU. The maximum absolute density value at any time point in the center and periphery of the SLNs was also significantly higher in metastatic SLNs compared to non‐metastatic ( P ≤ .001). With a cutoff value of 59.5 HU, the maximum absolute density value in the periphery of the SLN displayed high sensitivity and specificity (87.5% and 89.3%, respectively). The results of this study support the hypothesis that contrast enhanced CT imaging may aid in the assessment of SLN metastasis in dogs with mammary gland neoplasms.